Estimating the Age of Abandoned Alluvial Surfaces Using Morphologic Dating of Gully Incision. Issue 3 (8th March 2023) - Shmilovitz, Yuval; Shelef, Eitan; Wieler, Nimrod; Zhang, Huiping; Mushkin, Amit
Abstract: The age of abandoned alluvial surfaces is a key component in quantifying landscape evolution processes, tectonic activity, and paleoclimate. However, limited resources, restricted field accessibility, lacking dating material and analytical constraints are often encountered when dating such landforms. To help mitigate these limitations, we propose a new and complementary surface dating approach that is based on calculating the duration of gully incision into a surface since its abandonment using a locally calibrated landscape evolution model. The approach consists of calibration of incision model parameters for abandoned alluvial surfaces with known age and then using the calibrated model to calculate the time required for gully profiles to form on nearby undated alluvial surfaces as a proxy for surface abandonment. The approach was tested on previously dated late Pleistocene (34 and 70 ka) alluvial terraces in the hyper‐arid Negev desert (Israel). Calibrated model parameters were within the range reported for incision models in arid regions worldwide and late Pleistocene surface abandonment ages were recovered to within 10% accuracy. In contrast, modeled durations for gully incision into an older mid‐Pleistocene surface previously dated to 230–549 ka were grossly underestimated at <120 ka. Field observations and approach tests indeed indicated that late Pleistocene model parameters should not be extrapolated as‐is to model gully incision farther back through geologic time. Because the validity of the proposed ages depends on extrapolating the locally calibrated parameters of the incision model, we recommend that such dating be conducted with care and where assumptions will probably be valid. Plain Language Summary: An important feature for reconstructing paleoclimate and tectonic activity is determining the timing of when stream deposits were disconnected from the stream that deposited them to become abandoned alluvial surfaces. Here, we propose a new method for dating the abandonment of alluvial surfaces based on the age of gullies (erosional channels) incised into the surface after its abandonment as computed using a landscape evolution model. As a first step, the method requires calibration of the model parameters for a surface with an a priori known age. Based on the calibrated parameters, the model is then used to calculate the duration of the incision required to form observed gully profiles on nearby surfaces of unknown ages. The new approach was tested and successfully validated on previously dated alluvial surfaces in the Negev desert (Israel). Key Points: We proposed a morphologic approach for dating the abandonment of alluvial surfaces based on modeling gullies incised into them The proposed approach was successfully tested for multiple late Pleistocene surfaces in an arid study site in southern Israel The proposed modeling approach can help constrain changes in tectonic and climatic conditions for gully incision in both space and time